As percepções dos agricultores que cultivam soja transgênica no município de Não-Me-Toque - RS, Brasil: um estudo de caso mediante metodologia Q - Lima, Carina Petry (2005)
A study case was carried out in Brazil (Não-Me-Toque, RS), during the first semester of 2004, to know main reasons for farmers that could explain their acceptance to grow transgenic soy (ST). Q methodology was used to identify those reasons. This methodology combines in a unique way that is innovating- qualitative (deep interviews) and quantitative analysis (factor analysis). Seven people (extension agents, farmers and researchers) were interviewed in order to develop the set of statements (32) to be sorted by a small sample composed of 32 producers. The data was analyzed and interpreted using a special statistical software program called PCQ. The main reason for farmers to grow transgenic soy is that is an efficient way to combat weeps, and reduce costs, without affecting levels of production. Its diffusion took place not for pressure of great associations of producers or communication media. Sustainability of ST was considered at three levels: i) environmental (in a controversial way), legal, and structural.